2018
DOI: 10.1007/s00253-018-9261-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of oil-producing yeast Lipomyces starkeyi on glycerol carbon source based on metabolomics and 13C-labeling

Abstract: Lipomyces starkeyi is an oil-producing yeast that can produce triacylglycerol (TAG) from glycerol as a carbon source. The TAG was mainly produced after nitrogen depletion alongside reduced cell proliferation. To obtain clues for enhancing the TAG production, cell metabolism during the TAG-producing phase was characterized by metabolomics with C labeling. The turnover analysis showed that the time constants of intermediates from glycerol to pyruvate (Pyr) were large, whereas those of tricarboxylic acid (TCA) cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
10
1
Order By: Relevance
“…However, only a small amount of glycerol (only ~1.2% of the 13% of consumed glycerol), ended up as the backbone for the lipid fractions, with more being funnelled into de novo acyl chain synthesis, the majority of which ended up on the membrane lipids (Table 1). This contrasts with previous literature, in which the addition of glycerol was shown to induce TAG accumulation significantly in the diatom P. tricornutum (Villanova et al, 2017) and the oil‐producing yeast Lipomyces starkeyi (Maruyama et al, 2018) by increasing intracellular carbon intermediates of the Calvin–Benson cycle.…”
Section: Resultscontrasting
confidence: 98%
See 1 more Smart Citation
“…However, only a small amount of glycerol (only ~1.2% of the 13% of consumed glycerol), ended up as the backbone for the lipid fractions, with more being funnelled into de novo acyl chain synthesis, the majority of which ended up on the membrane lipids (Table 1). This contrasts with previous literature, in which the addition of glycerol was shown to induce TAG accumulation significantly in the diatom P. tricornutum (Villanova et al, 2017) and the oil‐producing yeast Lipomyces starkeyi (Maruyama et al, 2018) by increasing intracellular carbon intermediates of the Calvin–Benson cycle.…”
Section: Resultscontrasting
confidence: 98%
“…However, the assimilation pathways of glycerol into the microalgal lipidome are not yet fully understood. Previously, it has been shown that supplying exogenous glycerol can augment TAG production in diatoms (Villanova et al, 2017), yeast (Maruyama et al, 2018), and plant seeds (Pollard, Delamarter, Martin, & Shachar-Hill, 2015). TAG is composed of three fatty acyl chains linked to a glycerol backbone (glycerol-3-phosphate, G3P) via ester linkages.…”
Section: Introductionmentioning
confidence: 99%
“…The PPP was the unique supplier of NADPH. Indeed, the NADPH required for FA synthesis by L. starkeyi was majorly provided by PPP according to the C 13 metabolic flux analysis using C 13 -labeled glycerol as substrate [ 14 ]. The NADH generated during the metabolic process from glucose to acetyl-CoA was excessive and could not be used for FA synthesis according to the flux distribution analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A site-directed gene knockout strategy has been reported in L. starkeyi NRRL Y-11558 [ 11 ]. The development of synthetic biology approaches, coupled with the omics technologies [ 12 14 ], has continuously deepened the understanding of lipid metabolism of L. starkeyi [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic flux analysis with 13 C-labeled glycerol has been reported in previous studies (Alagesan et al, 2018;Maruyama et al, 2018;Tomàs-Gamisans et al, 2019;Toya et al, 2018;Yao et al, 2019), but, until now, has not been reported for S. cerevisiae. In the present study, to understand intracellular metabolism of S. cerevisiae obtained by ALE and the RIM15 disruptant grown on glycerol as a main carbon source, we performed metabolic flux analysis of evolved S. cerevisiae grown on a mixture of naturally-labeled and 13 C-labeled glycerol.…”
Section: Introductionmentioning
confidence: 93%